Dekonstruksi dalam Novel Azab Dan Sengsara Karya Merari Siregar - Ridwan; Asriadi (University of Brawijaya, 2025)
This research discusses Derrida's deconstruction theory which focuses on texts that build new meanings and reinforce existing meanings. The object of this research uses a novel entitled